Perceptions and expectations of medical doctors and nurses in Metro Manila on roles of pharmacists as Health professionals - Ramones, Rench Richmond J.; Tolentino, Ericko Paolo S.
In the past few years, the practice of pharmacy has expanded to include more patient-oriented services. Despite this, doctors and nurses may not always accept or recognize the wide scope of services that pharmacists can provide to improve patient care. This study aimed to investigate the perceptions of doctors and nurses in Metro Manila regarding the roles of pharmacists by assessing the level of interaction between pharmacists and doctors/nurses, their degree of comfort on various pharmacist functions, their expectations on these roles, and their perceptions on collaboration. The study employed a cross-sectional, descriptive research design consisting of 101 doctors and 98 nurses as respondents. Between doctors and nurses, doctors have far fewer interactions with pharmacists, with majority of them having an interaction only once a month. In general, doctors and nurses appear comfortable with pharmacists providing a broad range of services. However, they were more receptive of pharmacists' more traditional roles, e.g. detecting prescriptions errors, than of responsibilities that are clinical in nature, eg. Designing drug therapy regimens. Doctors and nurses highly expect pharmacists to be drug information experts, but a majority also expects them to work exclusively in drug supply management and dispensation. Furthermore, doctors and nurses recognize that collaboration with a pharmacist improves patient outcomes, and most are willing to accept the changes and perceived risks for the sake of collaboration, The doctors' perceived main barrier to collaboration is the lack of face-to-face communication, while nurses' main concern is that it takes too much time dispensation. Full acceptance and appreciation of pharmacists' expanded roles is related to the exposure doctors and nurses have had to those roles. Thus, there is a need for pharmacists to be involved in direct patient care activities where they can work alongside doctors and nurses to improve patient outcomes.
Undergraduate Thesis (BS in Industrial Pharmacy)--University of the Philippines Manila, 2015
Keywords: Pharmacists